25-Hydroxy Vitamin D Deficiency Is Associated With Cardiovascular Sequential Organ Failure Assessment and Pediatric Risk of Mortality III Scores in Critically Ill Children - Dang, Hongxing; Li, Jing; Liu, Chengjun; Xu, Feng (Frontiers in Pediatrics, 2020)
Aim: Investigate 25-hydroxy vitamin D ((25(OH)D) levels and the correlation with cardiovascular sequential organ failure assessment (CV-SOFA) and pediatric risk of mortality Ⅲ (PRISM-Ⅲ) scores in critically ill children. Methods: This prospective observational cohort study was conducted on consecutive critical ill children aged 1 month to 14 years old in 1 year. The blood sample was collected upon PICU admission. 25(OH)D deficiency was defined as<20 ng/mL. We performed univariate and multivariate analyses to evaluate associations with CV-SOFA and PRISM-Ⅲ scores and other important outcomes. Results: 296 critically ill children were enrolled in the study. The mean serum 25(OH)D level was 22.5 (IQR 16.3–31.8) ng/mL. The prevalence of 25(OH)D deficiency was 39.2% in critically ill children. 25(OH)D levels were significantly decreased in septic shock and associated with CV-SOFA and PRISM-Ⅲ scores. In multivariate analysis, vitamin D deficiency independently affected CV - SOFA and PRISM - Ⅲ scores, adjusted odds ratio: 2.106 (95% CI(1.076,4.124); p=0.03) and 4.94(95%CI (2.345,10.407); p<0.001), respectively. Conclusion：25(OH)D deficiency is prevalent in critically ill children at PICU admission and seems to be associated with higher CV-SOFA and PRISM-Ⅲ scores. Our study provides additional data for 25 (OH) D statuses that impact the outcomes of critically ill children.